2005
DOI: 10.1152/japplphysiol.00430.2004
|View full text |Cite
|
Sign up to set email alerts
|

Postural changes in lung volumes and respiratory resistance in subjects with obesity

Abstract: Reduced functional residual capacity (FRC) is consistently found in obese subjects. In 10 obese subjects (mean +/- SE age 49.0 +/- 6 yr, weight 128.4 +/- 8 kg, body mass index 44 +/- 3 kg/m2) without respiratory disease, we examined 1) supine changes in total lung capacity (TLC) and subdivisions, 2) whether values of total respiratory resistance (Rrs) are appropriate for mid-tidal lung volume (MTLV), and 3) estimated resistance of the nasopharyngeal airway (Rnp) in both sitting and supine postures. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
133
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 36 publications
15
133
2
6
Order By: Relevance
“…Our results confirm others in showing that TLC and RV are not significantly affected by weight loss or postural changes, 15,16,22 although modifications in TLC have been reported in some obese subjects. 5,[23][24][25] Other spirometric variables, such as VC and FEV 1 , increased significantly with weight loss induced by gastroplasty.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirm others in showing that TLC and RV are not significantly affected by weight loss or postural changes, 15,16,22 although modifications in TLC have been reported in some obese subjects. 5,[23][24][25] Other spirometric variables, such as VC and FEV 1 , increased significantly with weight loss induced by gastroplasty.…”
Section: Discussionsupporting
confidence: 91%
“…This longitudinal study confirms the sparse evidence in the literature of the different effects of body position on lung volumes depending on BMI range, as shown separately in the morbidly obese 15,16 and mildly to severely obese groups. 13,14,21 In non-obese subjects, the decrease in FRC upon adopting the supine position is essentially attributed to the gravitational effects of the abdominal contents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The effects of obesity on the lung function values have not been found to be consistent in earlier studies [58]. Other studies (other than from India) have reported effects of obesity on asthma [53], reduced FRC and expiratory reserve volume detected even at modest increase in weight [25], significant inverse relation between BMI and values of VC and TLC and the values of FRC and ERV decreasing exponentially with BMI [54], reduced FRC in obese subjects [55] and extreme obesity associated with a reduction in ERV, FVC, FEV 1 , FRC, FEF %, and MVV [56]. Several studies reported no significant differences in FEV 1 , FVC, FEV 1 /FVC ratio and FEF between obese and non-obese subjects [1,57,58].…”
Section: Discussionmentioning
confidence: 78%
“…A better understanding of the effects on obese patients of changing position from sitting to supine is important because the supine position is standard for sleep. The findings regarding the change in FRC and position vary between studies, with some investigators finding no change 9,10 and others 11 finding a decrease in the supine compared with the sitting position. One reason for these discrepancies between studies may relate to whether closing volume is taken into account.…”
Section: Introductionmentioning
confidence: 97%